2010
DOI: 10.1007/s11663-010-9381-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Hydrogen Solubility in Liquid Aluminum Alloys

Abstract: The modeling of hydrogen solubility in multicomponent Al-(Li, Mg, Cu, and Si) liquid phase has been performed with a thermodynamic approach using the modified quasichemical model with the pair approximation (MQMPA). All hydrogen solubility data available in literature was assessed critically to obtain the binary parameters of the MQMPA model for the Al-H, Li-H, Mg-H, Cu-H, Zn-H, and Si-H melts. For the Li-H system, a new thermodynamic description of the stable solid lithium hydride was determined based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 57 publications
(165 reference statements)
0
12
1
Order By: Relevance
“…The calculations made by Qiu et al [13] showed good agreement with experimental data for hydrogen solubility in fcc-Al and thermodynamic properties of AlH 3 . Later, thermodynamic modeling of hydrogen solubility in liquid Al was conducted by Harvey and Chartrand [15] using the MQM, showing better agreement with the available experimental data. Since MQM is used to describe the liquid phase in this work, the model parameters of Harvey and Chartrand [15] are used to describe the liquid phase in the present work.…”
Section: The Al-h Systemmentioning
confidence: 93%
See 3 more Smart Citations
“…The calculations made by Qiu et al [13] showed good agreement with experimental data for hydrogen solubility in fcc-Al and thermodynamic properties of AlH 3 . Later, thermodynamic modeling of hydrogen solubility in liquid Al was conducted by Harvey and Chartrand [15] using the MQM, showing better agreement with the available experimental data. Since MQM is used to describe the liquid phase in this work, the model parameters of Harvey and Chartrand [15] are used to describe the liquid phase in the present work.…”
Section: The Al-h Systemmentioning
confidence: 93%
“…Later, thermodynamic modeling of hydrogen solubility in liquid Al was conducted by Harvey and Chartrand [15] using the MQM, showing better agreement with the available experimental data. Since MQM is used to describe the liquid phase in this work, the model parameters of Harvey and Chartrand [15] are used to describe the liquid phase in the present work. The model parameters given by Qiu et al [13] for the AlH3 hydride and fcc-Al phase are also adopted in this work.…”
Section: The Al-h Systemmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, due to its high thermal diffusivity, the weld fusion and penetration are more difficult to achieve in comparison to steel [9]. The fast heat exchange implies also a fast solidification that leads to high stresses, resulting in cracks, pores formation or even complete break of the welded area [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%